Determinan konsumsi rumah tangga miskin di Kecamatan Dendang Kabupaten Tanjung Jabung Timur - Kartika Wahyu Ningsih; Syaparuddin Syaparuddin; Selamet Rahmadi (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
The purpose of this study was to determine the socioeconomic characteristics of poor households and the influence of household income, number of family members, household head education, social assistance status, and type of work of the head of the household on consumption of poor households in Dendang District. The data used are primary data obtained from questionnaires and direct interviews with a sample of 93. The sampling method used was random sampling. The data an alysis tools are used is descriptive and quantitative analysis’s with multiple linear analysis. The simultaneous results of multiple linear regression analysis that consumption of poor households in Dendang District are influenced by household head income, number of family members of the head of household, education of the head of the household, type of work of the head of the household and status of social assistance. While partially the household income variable and the number of family dependents have a significant effect on the consumption of poor households in Dendang Subdistrict, while the education of the head of the household, the type of work of the head of household and the status of social assistance do not have a significant effect on poor households in Dendang District. Keywords: Poor household consumption, household income, number of family members, education, social assistance status, and type of work.